Proceedings of the 4th ACM SIGCOMM Conference on Internet Measurement 2004
DOI: 10.1145/1028788.1028814
|View full text |Cite
|
Sign up to set email alerts
|

Reversible sketches for efficient and accurate change detection over network data streams

Abstract: Traffic anomalies such as failures and attacks are increasing in frequency and severity, and thus identifying them rapidly and accurately is critical for large network operators. The detection typically treats the traffic as a collection of flows and looks for heavy changes in traffic patterns (e.g., volume, number of connections). However, as link speeds and the number of flows increase, keeping per-flow state is not scalable. The recently proposed sketch-based schemes [14] are among the very few that can det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 23 publications
1
77
0
Order By: Relevance
“…The deltoid expands k-ary sketch with multiple counters for each bucket in the hash tables. The reverse hashing method further improves sketchbased change detection, which is more efficient and can infer the keys of culprit flows [22]. The work done by Xu et al [27] is closest to our work, in which traffic behavior profiling is conducted in real-time.…”
Section: Related Workmentioning
confidence: 76%
See 1 more Smart Citation
“…The deltoid expands k-ary sketch with multiple counters for each bucket in the hash tables. The reverse hashing method further improves sketchbased change detection, which is more efficient and can infer the keys of culprit flows [22]. The work done by Xu et al [27] is closest to our work, in which traffic behavior profiling is conducted in real-time.…”
Section: Related Workmentioning
confidence: 76%
“…Duffield et al [6] showed that even packet sampling is not scalable, especially after aggregation. There can be up to 2 64 flows defined by only considering source and destination IP addresses [22]. Recently, Cormode et al [4]'s deltoids and Krishnamurthy et al [11]'s k-ary sketch methods have been proposed for heavy change detection in high speed traffic.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, in this work, to identify the culprits, the original keys were kept temporarily. For real-world applications that must avoid high memory consumption to maintain the original keys, reversible sketches [23] can be efficiently applied. As the focus of our work is detection performance, we did not utilize or implement the reversible sketches.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the requirements above, we propose a new paradigm called DoS resilient High-speed Flow-level INtrusion Detection, HiFIND [18] leveraging recent work on data streaming computation and in particular, sketches [19,20]. Sketches are a kind of compact data streaming data structure which record traffic for given keys and are capable of reporting heavy traffic keys.…”
Section: Fifth Separating Anomalies From Intrusions For False Positimentioning
confidence: 99%
“…Although proposed in [19,20], sketches have not been applied to building IDSes for the following reasons:…”
Section: Fifth Separating Anomalies From Intrusions For False Positimentioning
confidence: 99%